Intensive processing optimization for achieving strong and ductile Al-Mn-Mg-Sc-Zr alloy produced by selective laser melting. (15th January 2021) - Bayoumy, D.; Schliephake, D.; Dietrich, S.; Wu, X.H.; Zhu, Y.M.; Huang, A.J.
Abstract: The Sc-containing AlMn alloy system produced by additive manufacturing (AM) has recently presented exciting new opportunities to achieve a step-change in mechanical properties, but its processability remains unclear. In this work, the optimum processing window for the Al-Mn-Mg-Sc-Zr alloy fabricated by selective laser melting (SLM) has been established for the first time. The window covers the range of processing parameters that can lead to a good combination of part density, strength, ductility, and processability. The alloys fabricated within this optimized processing window of SLM have the material relative density more than 99.8% with less porosity. Moreover, all these alloys have the yield strength exceeding 430 MPa and the ductility of over 17%. Further microstructural examinations suggest that such excellent mechanical properties are associated with a bimodal grain architecture. Also, a high number density of intermetallic particles has been detected in these two-grain regions. They are confirmed to be Al3 Sc and Mn(Fe)-rich quasicrystal. Most of these particles distributing along grain boundaries are expected to pin the grain boundaries and contribute to the high strength of this alloy. The findings will provide an essential basis for achieving exceptional mechanical performance and intricate geometry designs of the alloy using AM. Graphical abstract: Unlabelled Image Highlights: The optimum processing window for selective laser melted Al-Mn-Mg-Sc-Zr alloy has been established for the first time. Good combination of strength and ductility is attainable by using a wide range of laser energy inputs. The microstructure involves a unique bimodal grain structure and Al3 Sc and Mn(Fe)-rich quasicrystal phases.